Estudo e desenvolvimento de um algoritmo de detecção da operação ilhada para sistemas PV, aplicado a um microinversor baseado no conversor Zeta - Guisso, Igor Luiz (2015)
This work presents a study and a development of a microinverter, based on Zeta converter, as well as, the development of an islanding detection algorithm, based on the reduction of the maximum duty cycle of the converter. The objective is to achieve a reduction on the output voltage of the microinverter, so that it is possible to detect the islanding operation when the power grid is offline. In order to validate the proposed study the project of Zeta converter is presented, as well as, the implementation of the islanding algorithm in Matlab/Simulink® platform. The algorithm developed, in this project, presents outstanding results, since the variation of the microinverter output voltage amplitude resulted in an effective technique to detect islanding, as observed by simulations, which were performed in accordance with the standard IEEE 929.